Therapeutic Management of Transmissible Venereal Tumour in Dogs - Parikh, Naiya P; Panchal, Mahesh T; Parmar, Jignesh J; Ghodasara, Dinesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A total of 18 dogs affected with transmissible venereal tumour (TVT) were studied for therapeutic management under three groups each of 6 animals using vincristine alone (group 1), bacillus Calmette-Guerin alone (BCG) (group 2), and a combination of BCG and vincristine (group 3). Dogs having TVT were subjected to the confirmatory diagnosis using fine needle aspiration cytology (FNAC), impression smear and histopathological examinations prior to treatment. Treated dogs were monitored for their response to therapy with regards to physical regression of tumour masses along with histological changes. Complete regression of tumour masses was observed in the dogs treated with vincristine alone and combination of BCG and vincristine therapies. No such regression of tumour masses was observed in the dogs treated with BCG alone. Histologically the response of the tumour mass to the treatment was evinced by the appearance of macrophages and increased numbers of tumour infiltrating lymphocytes (TILs) followed by tumour cell apoptosis and necrosis with reduction in the mitotic index in group 1 and 3. The study indicated that combined therapy comprising BCG and vincristine was more effective than vincristine alone in treating TVT, however, BCG alone was not effective.